2020
DOI: 10.1177/0960327120916821
|View full text |Cite
|
Sign up to set email alerts
|

The role of 5-HT7 receptors on isoproterenol-induced myocardial infarction in rats with high-fat diet exacerbated coronary endothelial dysfunction

Abstract: The presence of 5-HT7r’s in both human and rat cardiovascular and immune tissues and their contribution to inflammatory conditions prompted us to hypothesize that these receptors contribute in acute myocardial infarction (MI) with underlying chronic endothelial dysfunction. We investigated the role of 5-HT7 receptors on heart tissue that damaged by isoproterenol (ISO)-induced MI in rats with high-fat diet (HFD). In vitro and in vivo effects of 5-HT7r agonist (LP44) and antagonist (SB269970) have been investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…5). The current findings are in covenant with the results observed by Cinar et al (2020) who found that IL-6 mRNA expression and 5-HT7 receptor mRNA expression levels increased in MI control. Elevation in the mRNA expression of 5-HT7 receptor and inflammatory cytokines (IL-6 and IL-1β) in the present research may be attributed to endothelial dysfunction due to damage of vascular tissues, through elevation of plasma TG, low-density lipoprotein, and Ox-LDL in the MI group as shown in Figure 3.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…5). The current findings are in covenant with the results observed by Cinar et al (2020) who found that IL-6 mRNA expression and 5-HT7 receptor mRNA expression levels increased in MI control. Elevation in the mRNA expression of 5-HT7 receptor and inflammatory cytokines (IL-6 and IL-1β) in the present research may be attributed to endothelial dysfunction due to damage of vascular tissues, through elevation of plasma TG, low-density lipoprotein, and Ox-LDL in the MI group as shown in Figure 3.…”
Section: Discussionsupporting
confidence: 91%
“…The reagent reaction mixture (25 µl) consisted of 12.5 µl of SYBR Green master mix (Thermo-Fisher ® Invitrogen TM ), cDNA template (1 µl), and primer pairs (0.25 µM). The sequence of primer pairs was obtained from Khan et al (2013) and Cinar et al (2020) for interleukin-6 (IL-6), IL-1β, and 5-hydroxytryptamine-7 receptor (5-HT7) (Table 1). Real-time PCR was performed with a Rotor-Gene ® MDx instrument programmed at 2 minutes at 50°C followed by 10 minutes at 95°C, 45 cycles (95°C for 20 seconds, 60°C for 30 seconds, and 72°C for 30 seconds), melting curve program (60°C-95°C).…”
Section: Gene Expression Analysis Of Il-6 Il-1β and 5ht-7mentioning
confidence: 99%
“…Total RNA was isolated from homogenized lung tissues following the instructions provided for the RNeasy Mini Kit (QIAGEN). cDNA was synthesized by reverse transcription of complementary DNA from isolated RNA samples according to the instructions of the High-Capacity cDNA Reverse Transcription Kit (Applied Biosystems, USA), as previously described [ 29 ]. The sequences of PCR primer pairs used for each gene are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The purity and concentration of the isolated RNA and cDNA were determined by a nucleic acid measurement. 24…”
Section: Rna Isolation and Cdna Synthesismentioning
confidence: 99%